2011
DOI: 10.1134/s0006297911050099
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of chaperone activity of proteins Hsp70 and Hdj1 in human leukemia U-937 cells after preconditioning with thermal shock or compound U-133

Abstract: Kinetics of the chaperone activity of proteins Hsp70 and Hdj1 were analyzed in human U-937 promonocytes during their response to heat shock or to treatment with the echinochrome triacetyl glucoside derivative U-133. To measure the chaperone activity of both proteins, a special test was developed for their recognition and binding of a denatured protein. Using this test, the chaperone activity could be concurrently estimated in large numbers of cellular or tissue extracts. We also estimated the contents of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…It was established that trisglucoside U-133 significantly increased Hsp70 expression in human erythroleukemia K562 cells [12]. The analysis of quantity and activity of cellular chaperones during the human leukemia U-937 cell response to heat stress or to the U-133 application showed that both factors caused the accumulation of chaperones with similar kinetics [13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was established that trisglucoside U-133 significantly increased Hsp70 expression in human erythroleukemia K562 cells [12]. The analysis of quantity and activity of cellular chaperones during the human leukemia U-937 cell response to heat stress or to the U-133 application showed that both factors caused the accumulation of chaperones with similar kinetics [13].…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we found that both heat shock and the U-133 substance were effective inducers of Hsp70, and the amount of the protein remained high during at least 24 h. The content of Hsp70 in the heattreated cells increased approximately 3 h earlier and the protein itself remained in the cells for a longer time than after the treatment with U-133 [13].…”
Section: U-133 Exhibits Anticancer Effect In Vivomentioning
confidence: 99%
“…The increase in the SWS duration and the decrease in the wakefulness duration were observed by us [9] in rats after the transfection of the VLPO neurons with the lentivector pLKO.1 shRNA Hdj1, which led to a 80% reduction in the level of co chaperone Hdj1 (HSP40 family). It is known that Hdj1 closely interacts with Hsp70, regulating its bind ing to the target protein [13].…”
mentioning
confidence: 99%
“…The increase in the SWS duration and the decrease in the wakefulness duration were observed by us [9] in rats after the transfection of the VLPO neurons with the lentivector pLKO.1 shRNA Hdj1, which led to a 80% reduction in the level of co chaperone Hdj1 (HSP40 family). It is known that Hdj1 closely interacts with Hsp70, regulating its bind ing to the target protein [13].Therefore, the increase in the SWS duration depends on the increase in the level of Hsp70 [8] and/or the decrease in the level of its co chaperone Hdj1 [9] in the sleep "center." These changes appar ently enhance the function of the inhibitory system in the VLPO on maintaining the wakefulness "centers" in the switched off state.…”
mentioning
confidence: 99%
“…È íàêîíåö, óñòàíîâëåíî, ÷òî ïîëèôåíîëàì ïðèñóùè è ðàçëè÷íûå ãåíîìíûå ýôôåêòû [11,16,29,71]. Èññëåäîâàíèÿ ïîñëåäíèõ ëåò ïîêàçàëè, ÷òî ìîäóëèðîâàòü ãåííóþ àêòèâíîñòü ñïîñîáåí è ýõèíîõðîì À [72,73,74,75].…”
unclassified